Prospective predictors of care partner burden and depression in Parkinson's disease. (22nd August 2022) - Whiteley, Nicole; Pluim, Celina F.; Split, Molly; Cabrera Tuazon, Angelie; Moore, Raeanne C.; Irene Litvan; Lessig, Stephanie; Filoteo, J. Vincent; Schiehser, Dawn M.
Abstract: Objectives: Care partners who provide informal care to individuals with Parkinson's disease (PD) report higher levels of burden and depression; however, longitudinal research on these symptoms is scarce. The current study assessed changes in care partner burden and depression, and patient and care partner predictors of these symptoms over time. Such knowledge may provide important information for assessment and treatment of depression and burden in care partners of individuals with PD. Research Design and Methods: Participants were 88 PD patients without dementia and their self‐identified care partner ( n  = 88). Care partners completed the Geriatric Depression Scale and Zarit Burden Interview. PD participants completed mood questionnaires and a motor exam at baseline and 2 year follow‐up. Relationships among care partner burden and depression over time with patient and care partner predictors (i.e., demographic, mood, and disease characteristics) were assessed using correlations and regression analyses. Results: Care partner burden and depression significantly increased over an approximate 2 year period. Greater baseline disease severity predicted worsening of care partner burden ( p  = 0.028), while baseline patient depression predicted worsening of care partner depression ( p  = 0.002). Conclusions: Results highlight differential impacts of specific PD symptoms on worsening care partner burden compared to depression; increased PD disease severity predicts increased burden, while patient mood predicts worsening of depression over time. Targeting PD disease severity and mood symptoms may prevent the progression of care partner burden and depression. Key points: Care partners who provide informal care to individuals with Parkinson's disease (PD) often report higher levels of burden and depression; however, longitudinal research on these symptoms is scarce. Study results revealed that both care partner burden and depression worsen over time, and are differentially predicted by specific PD symptoms. Greater baseline PD disease severity best predicted significant increases in care partner burden over an approximate 2 year period, while baseline patient depression was the primary predictor of increases in care partner depression over time. Findings suggest that interventions targeting PD disease severity and mood symptoms may prevent the progression of care partner burden and depression over time.